Active and Passive Facilitation Tendencies at Work Towards Sexy and Professional Women: The Role of Stereotypes and Emotions. Issue 2 (April 2023) - Cuadrado, Isabel; López-Rodríguez, Lucía; Brambilla, Marco; Ordóñez-Carrasco, Jorge L.
Stereotypes have important social consequences, such as promoting female discrimination in the workplace, which depends on how women are categorized. Extending prior work, here we analyze how two important female subgroups, women who are categorized as professional or sexy women, are evaluated on key dimensions of stereotype content (morality, sociability, and competence), positive and negative emotions, and facilitation behavioral tendencies (active and passive). To this end, we adapted a previous scale of facilitation tendencies to the working environment. Furthermore, we aim to explore the mechanism involved in carrying out helping behaviors towards each subgroup of women in the workplace. In order to fulfill these goals, 201 participants ( M age = 28.88, SD = 12.25; 66.2% women) were randomly assigned to evaluate a woman categorized as either sexy or professional on the mentioned variables. Results show that women categorized as sexy are devalued compared to those categorized as professionals. We also found that competence has a driving role in predicting more active facilitation tendencies towards a woman categorized as professional than a woman categorized as sexy via positive emotions. These findings have implications for the career development of women.